2020
DOI: 10.1186/s12884-020-2819-0
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for women who report domestic violence during and after pregnancy in low- and middle-income countries: a systematic literature review

Abstract: Background: Domestic violence is a leading cause of social morbidity and may increase during and after pregnancy. In high-income countries screening, referral and management interventions are available as part of standard maternity care. Such practice is not routine in low-and middle-income countries (LMIC) where the burden of social morbidity is high. Methods: We systematically reviewed available evidence describing the types of interventions, and/or the effectiveness of such interventions for women who repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 22 publications
1
32
0
Order By: Relevance
“…In LMIC, home violence in the form of interpersonal violence is particularly common, which is also re ected in our sample (51,52). Home violence was the only domain that signi cantly predicted cortisol, possibly because it is linked to consequences that are emotional in nature: isolation, fear, guilt, low self-esteem (53).…”
Section: Discussionsupporting
confidence: 51%
“…In LMIC, home violence in the form of interpersonal violence is particularly common, which is also re ected in our sample (51,52). Home violence was the only domain that signi cantly predicted cortisol, possibly because it is linked to consequences that are emotional in nature: isolation, fear, guilt, low self-esteem (53).…”
Section: Discussionsupporting
confidence: 51%
“…A search of the literature revealed most studies have been produced through North-North collaboration (e.g., US., UK, Europe, Canada), while LMICs are battling both a higher burden of violence and resource scarcity for effective interventions (Sapkota et al, 2019). To date, there has been little discussion about the detrimental effects of p-IPV from the South-South collaboration (Daley et al, 2020). Thus, this project provides an important opportunity to advance the comparative understanding of the difference of marital relationships and family functions between developed and less developed countries, and bridge the research gaps between East and West, providing a complement to global violence literature.…”
Section: Significance and Scopementioning
confidence: 99%
“…Thus, one of the critical issues is to develop or adapt instruments/indicators to reflect the 'latent trait' being assessed, which refers to the field of psychometric properties (i.e., reliability and validity). A recent systematic review of six interventions confirmed that screening, referral, and supportive counselling services are beneficial for abused women during pregnancy and after childbirth in LMICs (Daley et al, 2020). However, many barriers to IPV screening during antenatal check-ups have been documented, including low perception of the need to screen, feelings of distress, and difficulty disclosing (Duchesne et al, 2021).…”
Section: Summary Of Chapter and Current Knowledge Gapsmentioning
confidence: 99%
See 1 more Smart Citation
“…It may first occur or increase in frequency during the course of a pregnancy. 3 Universal screening efforts of traumatic injuries in emergency departments for partner violence have been recommended to maximize identification of survivors. 1 As experts on the maxillofacial region, oral and maxillofacial surgeons (OMSs) can play a prominent role in ensuring adequate screening and identification of partner violence in pregnant patients.…”
mentioning
confidence: 99%